IDENTIFY ABUSE STAY PERMIT BY FOREIGNERS IN INDONESIA - Annisa Niazela; Anita Herlina (Polteknik Imigrasi, 2020)
Abuse is applying something that is not what it should be. Foreigners often try this matter by violating the provisions of the time limit for a stay permit (overstay). Immigration law enforcement in this matter must really be enforced so that this matter does not happen again. Based on Law No. 6 of 2011 on Immigration, to prevent abuse of residence permits and law enforcement against foreigners who violate the requirements of a residence permit, monitoring of administrative completeness is intended for foreign citizens who enter Indonesian territory and take administrative actions. as well as legal remedies through a legal panel process. In this matter, it means to improve Human Resources (HR) in all aspects of immigration